2012
DOI: 10.2165/11598070-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Overt and Subclinical Hypothyroidism

Abstract: Hypothyroidism denotes deficient production of thyroid hormone by the thyroid gland and can be primary (abnormality in thyroid gland itself) or secondary/central (as a result of hypothalamic or pituitary disease). The term 'subclinical hypothyroidism' is used to define that grade of primary hypothyroidism in which there is an elevated thyroid-stimulating hormone (TSH) concentration in the presence of normal serum free thyroxine (T4) and triiodothyronine (T3) concentrations. Subclinical hypothyroidism may progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 86 publications
2
141
0
6
Order By: Relevance
“…[2][3][4][5] Hypothyroidism, either in overt or occult form, is the most common type with a prevalence of up to 20% in the elderly population. [6][7][8][9]13] Despite the fact that thyroid disorders are frequently encountered in Saudi Arabia, these conditions are understudied and there is a lack of information on their prevalence, types, and etiological factors contributing to their development. [26,27] The findings of the present study agree with the previous findings and show that the overall prevalence of thyroid disorders was 19.6%, suggesting that thyroid dysfunction is a common endocrine disorder in non-pregnant Saudi females, at least in the Western province of the kingdom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Hypothyroidism, either in overt or occult form, is the most common type with a prevalence of up to 20% in the elderly population. [6][7][8][9]13] Despite the fact that thyroid disorders are frequently encountered in Saudi Arabia, these conditions are understudied and there is a lack of information on their prevalence, types, and etiological factors contributing to their development. [26,27] The findings of the present study agree with the previous findings and show that the overall prevalence of thyroid disorders was 19.6%, suggesting that thyroid dysfunction is a common endocrine disorder in non-pregnant Saudi females, at least in the Western province of the kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The prevalence of thyroid disorders differs from one society to another and hypothyroidism is the most prevalent type with a reported frequency of 2-5% worldwide. [7,9] Also, the prevalence of subclinical hypothyroidism is approximately 4-8.5% and it can increase to up to 20% in women aged 60 years or older. [6,7,10] Alternatively, hyperthyroidism is less prevalent with a frequency ranging between 0.5 and 2% in women.…”
Section: Original Articlementioning
confidence: 99%
“…[12] The newly diagnosed hypothyroid group consisted of 4 overt hypothyroid cases (with serum TSH levels above 4.5 μIU/ml and low T4 levels), and 11 subclinical hypothyroid cases (with serum TSH levels between 4.5 and 10 μIU/ml and T4 levels within normal limits). [13] The serum testosterone levels of all 30 participants were within the normal range for the age group. A comparative analysis of both groups revealed that there was a statistically significant difference in the visual reaction time, auditory reaction time, and working memory scores, with the euthyroid group outperforming the hypothyroid group in all of these parameters.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous published studies have demonstrated the difficulty of maintaining patients in the guideline-recommended therapeutic range for TSH using levothyroxine, with as many as 32-48% of patients being categorized as having either a "subadequate" or "excessive" response to therapy [3,[43][44][45][46]. Factors affecting levothyroxine efficacy include patient persistence and compliance, medication tolerability, Since levothyroxine is an NTI drug, small differences in dose or blood concentration may lead to therapeutic failures or adverse drug reactions [4][5][6][7][8][9]47]. It is not surprising that patients, pharmacists, and physicians have been concerned regarding the use of generic NTI drugs with varying levels of potency [48], particularly in diseases such as hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Levothyroxine is classified as a narrow therapeutic index (NTI) medication, which indicates that small differences in absorption or bioavailability may lead to therapeutic failure or adverse drug reactions [4][5][6][7][8][9]. Currently, levothyroxine medications are available in various formulations, including compressed tablets (generic and branded) and soft gel caps.…”
Section: Introductionmentioning
confidence: 99%